Psychological treatments for psychosis: history and overview - Bachmann, Silke; Resch, Franz; Mundt, Christoph (The journal of the American Academy of Psychoanalysis and Dynamic Psychiatry, 2003)
This article is part of the ISPS (International Society for the Psychological Treatment of the Schizophrenias and other Psychoses) task force report on the PORT (Patients Outcome Research Team) recommendations for treatment of schizophrenia. It reviews psychological treatment approaches in psychosis to date and assesses recent trends. The most influential therapies have been psychoanalytic/psychodynamic, cognitive behavioral (CBT), and supportive therapy.
Gesehen am 07.12.2020